2021
DOI: 10.3389/fnmol.2021.695873
|View full text |Cite
|
Sign up to set email alerts
|

The Metallome as a Link Between the “Omes” in Autism Spectrum Disorders

Abstract: Metal dyshomeostasis plays a significant role in various neurological diseases such as Alzheimer’s disease, Parkinson’s disease, Autism Spectrum Disorders (ASD), and many more. Like studies investigating the proteome, transcriptome, epigenome, microbiome, etc., for years, metallomics studies have focused on data from their domain, i.e., trace metal composition, only. Still, few have considered the links between other “omes,” which may together result in an individual’s specific pathologies. In particular, ASD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 200 publications
1
10
0
Order By: Relevance
“…Moreover, in PZD mice, changes in expression levels of interleukins in the brain suggest the presence of neuro-inflammatory processes [ 99 ]. While these findings in PZD mice link zinc deficiency, GI and immune system abnormalities to brain pathology and ASD behavior ( Figure 1 ), a similar study in humans has not been conducted so far and highlights the need for multi-omics approaches in ASD [ 24 ].…”
Section: Prenatal Zinc-deficient Micementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in PZD mice, changes in expression levels of interleukins in the brain suggest the presence of neuro-inflammatory processes [ 99 ]. While these findings in PZD mice link zinc deficiency, GI and immune system abnormalities to brain pathology and ASD behavior ( Figure 1 ), a similar study in humans has not been conducted so far and highlights the need for multi-omics approaches in ASD [ 24 ].…”
Section: Prenatal Zinc-deficient Micementioning
confidence: 99%
“…Further, an elevation of copper in samples of subjects with autism [ 21 ] was reported, and the Cu/Zn ratio found increased in subjects with autism [ 22 , 23 ]. Based on recent data, zinc deficiency, especially maternal zinc deficiency during pregnancy, may be a risk factor for ASD in humans [ 15 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data implicate metal dyshomeostasis and abnormalities of the "metallome" (i.e., binding, distribution and metabolic handling of trace metals) in the pathogenesis of ASD [1][2][3][4][5][6]. For example, elevated blood levels of copper and an increased ratio of copper to zinc have been reported in children with ASD and proposed as potential biomarkers of this disorder [1][2][3]5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Data implicate metal dyshomeostasis and abnormalities of the "metallome" (i.e., binding, distribution and metabolic handling of trace metals) in the pathogenesis of ASD [1][2][3][4][5][6]. For example, elevated blood levels of copper and an increased ratio of copper to zinc have been reported in children with ASD and proposed as potential biomarkers of this disorder [1][2][3]5,6]. Copper is a redox-reactive metal that acts as a cofactor in many electron transfer reactions, whose free concentration must be maintained within a safe narrow range in order to prevent dysregulated oxidation of proteins and lipids due to elevated levels.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the theory above, Ma et al [91] prepared Ag44(SR)30 silver nanoclusters with a ligand of 5-mercapto-2-nitrobenzoic acid, and completed the high precision detection of GSH, which enables more accurate and comprehensive diagnosis and assessment of Parkinson's disease. It had been reported that autism spectrum disorders (ASD) were also associated with GSH [92][93][94][95]. The research found that both reduced GSH and total GSH levels were lower in the ASD group than that in the control group [96].…”
Section: Nano-drug Design Based On the Role Of Gsh In Neurological Diseasesmentioning
confidence: 91%